IMPLEMENTASI METODE REGRESI LINIER BERGANDA UNTUK MEMPREDIKSI KINERJA KARYAWAN PT. TIMBANG DELI - Sinaga, Anita Sindar RM (ScientiCO : Computer Science and Informatics Journal, 2021)
PT. Timbang Deli is a company engaged in the management of oil palm plantations. The productivity of a company is highly dependent on the implementation of the duties and responsibilities of each employee. Prediction of employee performance aims to increase the effectiveness of the division of tasks that affect employee rewards. The analysis stage of the system is built in the first stage of analysis for defining requirements. The second stage is designing a graphic interface for the display of each requirement. In the third stage, all application support functions such as access rights, employee data input, and graphical interfaces are integrated into a complete set of program codes. The prediction system is built based on the web using the Multiple Linear Regression method with the variables Punctuality (X1), Target Achievement (X2), Task Implementation (X3), Teamwork (X4), Responsibility (X5). Prediction results show the percentage of each employee's performance.